Intracranial meningioma in two coeval adult cats from the same litter. Issue 2 (July 2021) - Orgonikova, Ivona; Mari, Lorenzo; Giannasi, Chiara; Batlle, Martí Pumarola i; Behr, Sebastien; Brocal, Josep
Case summary: In this report we describe the occurrence of intracranial meningioma in two adult cats from the same litter. The location of the meningioma varied: one tumour was at the level of the brainstem, and the other was affecting the temporal and piriform lobes. The cat with the brainstem meningioma was treated with radiotherapy and the littermate had a rostrotentorial craniectomy for tumour removal. Both cats had a histopathological diagnosis of grade I meningioma of a predominantly fibrous subtype. Relevance and novel information: Cases of familial meningioma in cats have not previously been described in the veterinary literature. However, familial meningioma is well described in humans and it is possible that cases are underestimated in animals. We discuss the possible genetic background and other causes, as well as challenges we may face in veterinary medicine in identifying these associations.